2011
DOI: 10.1182/blood-2011-07-368514
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma mucins trigger reciprocal activation of platelets and neutrophils in a murine model of Trousseau syndrome

Abstract: Trousseau syndrome is classically defined as migratory, heparin-sensitive but warfarin-resistant microthrombi in patients with occult, mucinous adenocarcinomas. Injecting carcinoma mucins into mice generates platelet-rich microthrombi dependent on P-and L-selectin but not thrombin. Heparin prevents mucin binding to P-and L-selectin and mucininduced microthrombi. This model of Trousseau syndrome explains resistance to warfarin, which inhibits fluid-phase coagulation but not selectins. Here we found that carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 54 publications
3
95
0
3
Order By: Relevance
“…Moreover, we observed an association between D-dimer level and serum CA-125 level. A significant increase in CA-125 levels has been reported in mucin-producing tumors, and TS is known to occur in association with such tumors (2,6). We observed that tumors with mucin-producing characteristics exhibited an association between the levels of D-dimer and serum CA-125 (parallel change) in TS.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, we observed an association between D-dimer level and serum CA-125 level. A significant increase in CA-125 levels has been reported in mucin-producing tumors, and TS is known to occur in association with such tumors (2,6). We observed that tumors with mucin-producing characteristics exhibited an association between the levels of D-dimer and serum CA-125 (parallel change) in TS.…”
Section: Discussionsupporting
confidence: 59%
“…The development of a novel marker to diagnose Trousseau's syndrome is required. Several mechanisms have been proposed to explain the occurrence of hypercoagulation in patients with malignancy, including thromboplastin-like substances, fibrin deposition, direct factor X activation by tumor proteases, tissue factor, cysteine protease, tumor hypoxia, tumor-induced inflammatory cytokines and carcinoma-associated mucins (1,(8)(9)(10). Among them, mucins are thought to trigger this syndrome (9,10).…”
Section: A B C Dmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the occurrence of hypercoagulation in patients with malignancy, including thromboplastin-like substances, fibrin deposition, direct factor X activation by tumor proteases, tissue factor, cysteine protease, tumor hypoxia, tumor-induced inflammatory cytokines and carcinoma-associated mucins (1,(8)(9)(10). Among them, mucins are thought to trigger this syndrome (9,10). The serum tumor markers CA19-9 (also known as MUC-1/Y), CA125 (also known as MUC-16) and CA15-3 (also known as MUC-1) are well known tumor-associated mucins; these are large, heavily glycosylated molecules that are resistant to denaturation, boiling and proteases (11).…”
Section: A B C Dmentioning
confidence: 99%
“…Bazı akut lösemilerde, over, mide ve böbrek solid tümörlerinde prokoagülan olarak doku faktörünün arttığı ve akciğer, kolon, meme, böbrek kanserlerinde ve lösemilerde prokoagülan olan sistein proteinaz tarafınca direkt faktör X aktivasyonu yapıldığı gösterilmiştir (27,28). Musin sekrete eden adenokarsinomlarda ise sialik asitin faktör X'u aktifleştirdiği ve dolayısıyla akciğer, pankreas, gastrointestinal sistem ve over adenokarsinomlarında venöz tromboz riskinin arttıtığı ortaya konmuştur (29)(30)(31)(32)(33). Diğer bir mekanizma olan damar duvarı hasarında; kanser hücreleri direkt damar invazyonu yaparak endotel bütünlüğünü bozmanın yanı sıra damar geçirgenliğini bozan faktörlerin sentezine yol açarak fibrinojen ve pıhtılaşma proteinlerinin toplanmasına neden olurlar (34).…”
Section: Gereç Ve Yöntemunclassified